Pengaruh Mindset Terhadap Self-Concept Siswa di SMP Negeri 1 Hiliserangkai - Kurniawan Hulu; Jonisman Kristian Laoli; Hosianna Rodearni Damanik (Indo-MathEdu Intellectuals Journal, 2023)
Mindset Is a way of thinking that is formed from beliefs that affect one's behavior and attitude. Self-concept is a person's view of himself which includes a picture of himself, and the desired personality obtained from the results of experiences and interactions that include physical or psychological aspects. This study aims to determine the influence of Mindset on students' Self-concept. The method used in this study is a quantitative associative method by selecting a sample of 30 grade VIII-D students at SMP Negeri 1 Hiliserangkai. The data collection instrument is a questionnaire with Likert scale. Data analysis using the correlation coefficient with the Product Moment formula and calculations using SPSS for windows data processing obtained results of 0.648 and the coefficient of determination obtained an R Square of 42.0%. The influence of variable X (Mindset influence) on variable Y (student self-concept) can be proven from the calculation results obtained from calculations using the t test. The result of the calculation of tcalculate is substituted by the magnitude of the ttable value. Where t_hitung=4.502 does not lie in the interval: 1.701≤t≤1.701, or in other words the value of tcount = 4.502 > 1.701 then declare Ho rejected and accept Ha accepted. So, the hypothesis that reads: "there is a significant influence between Mindset on Self-concept students" is accepted at a significant level of 5%.